A sampling plan for Liriomyza huidobrensis (Diptera: Agromyzidae) on a potato (Solanum tuberosum) plantation - Alves, Flávia M.; Silva, Ítalo Willian da; Fernandes, Flávio L.; Fernandes, Flávio L.; Gorri, Jéssica E. R.; Diniz, Juno F. S. (American Journal of Potato Research, 2014)
No sampling plans specifically developed for mines associated with the pest Liriomyza huidobrensis in potato fields have been published to date. Thus, the objectives of this study were to determine the sampling unit and to establish the number of samples needed for the application of this study’s sampling plan. For this purpose, we evaluated 16 commercial fields of the potato cultivar Agata (24.5 ha). We evaluated the number of mines located in the apical, middle, and basal canopy-sections of plants. Higher mine densities were found in the leaves in the middle and basal section of plants than in the apical section. The middle canopy-section was best suited for sampling the mines. The result showed that the negative binomial distribution fit the mine density of L. huidobrensis. Fifteen samples/24.5 ha was determined to be appropriate for use in conventional sampling. The cost for sampling was US $ 5.32 per ha. The cost of performing the sampling was significantly lower than the cost of insecticide application.
Keywords: Leafminer; Conventional; Integrated pest management; Horticulture